Communication Technology Rebuilding A Better Global Civilization on Earth - Sirken, Faustinus (IPTEK The Journal for Technology and Science, 2024)
The disruption of communication technology causes humans to continue to reflect on who they are and how they view the world. The more humans utilize communication technology that continues to change, the more they will examine their existence and the model of social interaction that underlies their lives, and the greater the opportunity for humans to shape communication technology in ways that improve the world situation. Humans reflect on themselves as sources of authority and meaning. Liberals with a subjectivist view emphasize the experiences that occur within humans, so humans must find within themselves the meaning of everything that happens so that they can inspire meaning for the universe. Meanwhile, Dataist with an intersubjectivity view emphasize that meaning occurs in a network of stories mutually told among many people in one world as an experience of one individual. Thus, the essence of humanism in the experience of intersubjectivity reflects humans as a source of authority and meaning occurring in a network of stories told to each other among many people worldwide. The acceleration of communication technology, especially computer algorithms, is used to read stories told by many people in one world, analyze the structure or elements of each story, and turn the stories of many people into wisdom for a better global civilization on Earth. Based on the above reasoning, this article offers a solution to efforts to rebuild global civilization on Earth with the contribution of computer algorithms. Optimally, communication technology with intelligent computer algorithms strengthens the social order, bringing global citizens closer together as one human civilization. The empowerment of communication technology through computer algorithms creates a better global civilization by implementing the values of freedom and equality for humanity. The research method uses a phenomenological methodology, while the theoretical framework uses intersubjective theory and data theory.